Long-Term Pediatric Outcomes of Decompressive Craniectomy after Severe Traumatic Brain Injury - Ocasio-Rodríguez, Claudia M.; Puig-Ramos, Anabel; García-De Jesús, Ricardo (Puerto Rico Health Sciences Journal, 2023)
Objective: There is no consensus on the use of decompressive craniectomy (DC) to manage severe traumatic brain injury (sTBI). We evaluated the profile of pediatric patients admitted with sTBI and assessed functional outcomes, 6 months posttrauma, in patients who had a DC and in those who had not, and the functional outcomes of early versus late DCs. Patients and Methods: This case-control observational study evaluated pediatric patients admitted for sTBI in Puerto Rico (June 2016-October 2018); we included patients admitted within 24 hours of injury and had a Glasgow Coma Scale (GCS) of 8 or lower. 6-month post trauma outcomes were measured with the Glasgow Outcome Scale Extended Pediatric (GOS-E Peds). Results: 20 patients were included; 15 underwent a DC and 5 comprised the control group. We found no differences in terms of sex, age, GCS score, Pediatric Risk of Mortality score, or Pediatric Trauma Score. However, in the DC group, a higher percentage of patients presented significant cerebral herniation in the initial computed tomography scan (CT) (DC: 73%; control: 0%; P = .005). No differences were found regarding intracranial pressure (ICP), cerebral perfusion pressure, mean arterial pressure, PaCO2, or temperature. Patients in the DC group had longer hospital stay (DC: 41; control: 17 days; P = .0005). All patients with DC survived, with an early procedure being associated with favorable outcomes. Conclusion: As determined 6 months post-trauma, this study showed that early DC increased survival and improved functionality.